Influence of KCl and HCl on high temperature corrosion of HVAF-sprayed NiCrAlY and NiCrMo coatings - Sadeghimeresht, Esmaeil; Reddy, Liam; Hussain, Tanvir; Huhtakangas, Matti; Markocsan, Nicolaie; Joshi, Shrikant (Elsevier, 2018)
The oxidation performance of NiCrAlY and NiCrMo coatings thermally sprayed by high velocity air-fuel (HVAF) technique has been investigated in a chloridizing-oxidizing environment, with and without a KCl deposit, at 600 °C for up to 168 h. Both coatings protected the substrate in the absence of KCl due to formation of a dense Cr-rich oxide scale. In the presence of KCl, Cl−/Cl2 diffused through a non-protective and porous NiCr2O4 scale formed on NiCrAlY, leading to formation of volatile CrCl3. On the other hand, Mo in NiCrMo stimulated the formation of a more protective Cr-rich oxide scale which increased the corrosion resistance by reducing Cl−/Cl2 diffusion.